GE_GERICHTE C/25954/2012 vom 12. Juli 2013 - GE Cour de justice (2013)
; QUALITÉ POUR RECOURIR ; ASSEMBLÉE GÉNÉRALE ; INTÉRÊT DIGNE DE PROTECTION ; AMENDE | CPC.128.2. CPC.311. CO.699. CO.740.5. CP.292